Bimetal organic gel electrode material suitable for wide power fluctuation and preparation method and application thereof
By using bimetallic organic gel electrode materials, the problems of slow reaction kinetics and high overpotentials in existing electrolytic water technology are solved, and efficient electrocatalytic hydrogen evolution and oxygen evolution under wide power fluctuations are achieved, reducing energy consumption and hydrogen production costs.
Patent Information
- Application Number
- CN202411840472.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The existing electrolytic technology has slow reaction kinetics during hydrogen evolution and oxygen evolution, resulting in high overpotentials, high energy consumption, high hydrogen production cost, and difficult to adapt to wide power fluctuations.
Bimetallic organic gel electrode material is used to regulate the molar ratio of nickel and cobalt, improve the conductivity and electrocatalytic performance of the material, and enhance the adaptability to wide power fluctuations. The material is synthesized by the heat injection method to form a structure with more defects and a larger specific surface area, which promotes the transport of reaction intermediates.
Electrocatalytic hydrogen evolution and oxygen evolution activities that maintain high stability under wide power fluctuations are achieved, reducing overpotentials, improving energy efficiency, and reducing hydrogen production costs.
Smart Images

Figure CN119661865A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemical catalytic hydrogen production, and in particular relates to a bimetallic organic gel electrode material suitable for wide power fluctuations, a preparation method and an application thereof. Background Art
[0002] With the comprehensive green transformation of my country's economic and social development, renewable energy such as solar energy, wind energy and tidal energy have ushered in a huge wave of development. However, during use, due to the volatility and intermittency of renewable energy supply, it is impossible to provide a continuous and stable energy supply. In this case, renewable energy is combined with energy storage systems to solve the problems of wind and light abandonment caused by power fluctuations in intermittent power generation and insufficient grid absorption capacity. At present, photovoltaic power generation and wind power generation mainly rely on high-efficiency batteries for energy storage. However, batteries have limitations such as low energy density and short storage time, which restricts their further application and development. In contrast, hydrogen energy storage has the advantages of high mass energy density and long storage time, so it is becoming an efficient way to regulate, store and convert energy.
[0003] Hydrogen energy is a high-energy-density, clean, environmentally friendly and renewable energy carrier. Using renewable energy to electrolyze water to produce hydrogen can achieve zero carbon emissions from the source and generate high-purity hydrogen. It is a technical focus for efficiently utilizing renewable energy, accelerating the development of hydrogen energy and achieving the "dual carbon" goal. At present, the slow reaction kinetics in the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) are the main problems facing the development of water electrolysis, which will produce a high overpotential. Therefore, reducing energy consumption and compressing the cost of hydrogen production are important ways to achieve sustainable and large-scale development of the hydrogen energy industry. At the same time, the development of water electrolysis systems suitable for wide power fluctuations can effectively alleviate the problems of wind and light abandonment in wind and solar complementary power generation systems, and effectively improve energy utilization. Since both HER and OER are composed of multi-step reactions, including the adsorption and desorption of reaction molecules, the transfer of electrons, and the formation and diffusion of generated gases, this puts forward requirements for the intrinsic activity of the catalyst. Although traditional precious metal electrocatalysts have good catalytic activity, their large-scale application is seriously restricted due to their shortage of reserves and high cost. To overcome these problems, the development of efficient, stable, and low-cost electrocatalysts is crucial.
[0004] Metal organic gel (MOG) is an emerging electrochemical material and a coordination-driven supramolecular polymer. Its uniqueness lies in that metal ions and ligands first generate gel factors through self-assembly, and then the fibrous, sheet-like or granular gel factors further form an interlaced three-dimensional network structure through intermolecular forces such as intermolecular hydrogen bonds, π-π stacking and van der Waals forces. However, the electronic conductivity of MOG is generally low. The MOGs reported so far mostly focus on the coordination of a metal ion and ligand, which greatly limits their coordination with the central metal atom and the controllability of the structure. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a bimetallic organogel electrode material that is adaptable to wide power fluctuations. The bimetallic organogel electrode material not only increases the exposure ratio of metal active sites, but also improves the conductivity and electrocatalytic performance of the bimetallic organogel electrode material, and still has high stability under large current density fluctuations (i.e., wide power fluctuations).
[0006] Another object of the present invention is to provide a method for preparing a bimetallic organic gel electrode material, wherein the preparation method adjusts the molar ratio of the two metals to obtain the bimetallic organic gel electrode material by hot injection reaction of a salt solution of transition metals cobalt and nickel and terephthalic acid.
[0007] Another object of the present invention is to provide a bimetallic organic gel electrode material suitable for wide power fluctuations for use in hydrogen or oxygen evolution.
[0008] The purpose of the present invention is achieved through the following technical solutions.
[0009] A method for preparing a bimetallic organic gel electrode material comprises the following steps:
[0010] A transition metal nickel salt and a transition metal cobalt salt are dissolved in ethanol to obtain a transition metal salt mixture. The transition metal salt mixture is added dropwise to a terephthalic acid mixture at 70 to 90° C. (using a hot injection method) under a nitrogen or inert gas atmosphere, and the solvent thermal reaction is continued at 70 to 90° C. for 3 to 5 hours to obtain a colloidal suspension. The precipitate is centrifuged to obtain a precipitate, which is washed and vacuum dried to obtain a bimetallic organic gel electrode material, wherein the ratio of nickel in the transition metal nickel salt, cobalt in the transition metal cobalt salt and terephthalic acid in the terephthalic acid mixture is x:y:(x+y), x=1 to 2, y=1 to 2.
[0011] In the above technical solution, the transition metal cobalt salt is cobalt nitrate hexahydrate or cobalt chloride, and the transition metal nickel salt is nickel nitrate hexahydrate or nickel chloride.
[0012] In the above technical solution, the ratio of the molar fraction of nickel in the transition metal nickel salt to the volume fraction of ethanol is (1-2):(20-60), the unit of the molar fraction is mmol, and the unit of the volume fraction is mL.
[0013] In the above technical solution, the terephthalic acid mixed liquid is a mixture of terephthalic acid and dimethyl sulfoxide, and the concentration of terephthalic acid in the terephthalic acid mixed liquid is 0.5-1 mM.
[0014] In the above technical solution, the transition metal nickel salt and the transition metal cobalt salt are dissolved in ethanol by ultrasound for 30 to 60 minutes.
[0015] In the above technical solution, the terephthalic acid mixture is first stirred at 70-90°C for at least 30 minutes, and then the transition metal salt mixture is added dropwise to the terephthalic acid mixture at 70-90°C by hot injection. The terephthalic acid mixture is kept stirred when the transition metal salt mixture is added dropwise to the terephthalic acid mixture.
[0016] In the above technical solution, the nitrogen or inert gas atmosphere is achieved by replacing the nitrogen or inert gas at least three times, wherein the operation of replacing the nitrogen or inert gas includes: evacuating to -0.1 to -0.01 MPa, and introducing nitrogen or inert gas.
[0017] In the above technical solution, the washing operation includes: centrifuging the precipitate 3 to 5 times with ethanol and dimethyl sulfoxide respectively.
[0018] In the above technical solution, the vacuum drying temperature is 60 to 90° C., and the vacuum drying time is 12 to 24 hours.
[0019] The bimetallic organic gel electrode material obtained by the above preparation method.
[0020] Application of the above bimetallic organic gel electrode material in hydrogen evolution or oxygen evolution.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The bimetallic organogel electrode material of the present invention has excellent proton conductivity and electron conductivity, is beneficial to the reaction of reaction intermediates such as H ions and the transmission of electrons, and is conducive to electrocatalytic hydrogen evolution. The bimetallic organogel electrode material of the present invention has excellent electrocatalytic hydrogen evolution and oxygen evolution activity.
[0023] (2) The bimetallic organic gel electrode material of the present invention has a low overpotential in the HER process in an alkaline environment, with the lowest overpotential being 28 mV, and still maintains good stability under different high current densities, and has good electrochemical activity and wide power stability.
[0024] (3) The preparation method of the present invention synthesizes the bimetallic organogel electrode material by a hot injection method. Due to the difference in the atomic radius of the two metals, the bimetallic organogel electrode material contains more defects and a larger specific surface area, which promotes the transport process of the reaction intermediates inside it and effectively increases the HER reaction kinetics.
[0025] (4) The preparation method of the present invention has simple process, low cost, is suitable for large-scale commercial production, and is environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The scanning electron microscope (SEM) images of the bimetallic organic gel electrode materials prepared in Examples 1 to 3, wherein (a) is Example 1, (b) is Example 2, and (c) is Example 3;
[0027] Figure 2 High-resolution transmission electron microscopy (HRTEM) images of bimetallic organogel electrode materials prepared in Examples 1 to 3, wherein (a) is Example 1, (b) is Example 2, and (c) is Example 3;
[0028] Figure 3 XRD diagrams of the bimetallic organic gel electrode materials prepared in Examples 1 to 3 and the metal organic gel materials prepared in Comparative Examples 1 to 2;
[0029] Figure 4 Fourier transform infrared spectra (FTIR) of the bimetallic organogel electrode materials prepared in Examples 1 to 3;
[0030] Figure 5 The Raman spectra of the bimetallic organic gel electrode materials prepared in Examples 1 to 3 are shown in FIG.
[0031] Figure 6 This is an element distribution mapping characterization diagram of the bimetallic organic gel electrode material prepared in Example 1;
[0032] Figure 7 The hydrogen evolution reaction-polarization curve (HER-LSV) of the bimetallic organogel electrode material prepared in Examples 1 to 3;
[0033] Figure 8 The hydrogen evolution reaction-polarization curves (HER-LSV) of the metal organic gel material prepared in Comparative Examples 1 to 2, the metal organic compound material prepared in Comparative Examples 3 to 4, and the bimetallic organic compound material prepared in Comparative Example 5;
[0034] Fig. 9The Tafel curves of the hydrogen evolution reaction of the bimetallic organic gel electrode materials prepared in Examples 1 to 3;
[0035] Fig.10 The Tafel curves of the hydrogen evolution reaction of the metal organic gel material prepared in Comparative Examples 1 to 2 and the metal organic compound material prepared in Comparative Examples 3 to 4;
[0036] Fig.11 The Tafel curve of the hydrogen evolution reaction of the bimetallic organic compound material prepared in Comparative Example 5;
[0037] Fig.12 The bimetallic organic gel electrode material prepared in Example 1 has a conductivity of 10 mA cm -2 Voltage test diagram of hydrogen evolution reaction maintained at current density for 175h;
[0038] Fig.13 The metal organic gel material prepared in Comparative Examples 1 to 2 and the metal organic compound material prepared in Comparative Examples 3 to 4 were subjected to 10 mA cm -2 The voltage test diagram of hydrogen evolution reaction maintained at the current density for 10 hours;
[0039] Fig.14 The bimetallic organic compound material prepared in Comparative Example 5 has a -2 The voltage test diagram of hydrogen evolution reaction maintained at the current density for 10 hours;
[0040] Fig.15 The bimetallic organic gel electrode material prepared in Example 1 has a high conductivity at 100, 200, and 400 mA cm -2 Voltage test diagram of hydrogen evolution reaction maintained for 65 hours under current density fluctuation;
[0041] Fig.16 Oxygen evolution reaction-polarization curve (OER-LSV) of the bimetallic organic gel electrode material prepared in Examples 1 to 3;
[0042] Fig.17 These are EIS impedance test graphs of the bimetallic organic gel electrode materials prepared in Examples 1 to 3 and the metal organic gel materials prepared in Comparative Examples 1 to 2. DETAILED DESCRIPTION
[0043] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0044] In the following examples, Nafion solution (5 wt %) was purchased from Rowan Reagent Company, and the concentration of perfluorosulfonic acid polymer (Nafion) in the Nafion solution (5 wt %) was 5 wt %.
[0045] In the following examples, a French Bio-Logic electrochemical workstation SP-150e (dual channel) was used to perform linear sweep voltammetry (LSV) tests and hydrogen evolution stability tests.
[0046] In the following embodiments, nitrogen atmosphere is achieved by replacing nitrogen three times, and the operation of replacing nitrogen includes: evacuating to -0.1 MPa and introducing nitrogen.
[0047] Examples 1 to 3
[0048] A method for preparing a bimetallic organic gel electrode material comprises the following steps:
[0049] A transition metal nickel salt, a transition metal cobalt salt and ethanol are mixed and ultrasonicated for 30 minutes to dissolve the transition metal nickel salt and the transition metal cobalt salt in ethanol to obtain a brown transparent transition metal salt mixture. Under a nitrogen atmosphere, a colorless transparent terephthalic acid mixture is placed in a round-bottom flask and stirred for 30 minutes under a 70°C heating jacket. Then, under stirring conditions, the transition metal salt mixture is slowly added dropwise to the terephthalic acid mixture at 70°C by a hot injection method, and the solvent thermal reaction is continued at 70°C for 3 hours under stirring conditions to obtain a uniform colloidal suspension. The suspension is centrifuged to obtain a precipitate, and the precipitate is washed 5 times each with ethanol and dimethyl sulfoxide in sequence. , washed and then dried at 85° C. in vacuum for 20 h to obtain a bimetallic organic gel electrode material, wherein the transition metal cobalt salt is cobalt nitrate hexahydrate, and the transition metal nickel salt is nickel nitrate hexahydrate, wherein, in terms of molar fractions, the ratio of nickel (Ni) in the transition metal nickel salt, cobalt (Co) in the transition metal cobalt salt and terephthalic acid in the terephthalic acid mixture is G, the ratio of the molar fraction of nickel in the transition metal nickel salt to the volume fraction of ethanol is W, the unit of the molar fraction is mmol, the unit of the volume fraction is mL, the terephthalic acid mixture is a mixture of terephthalic acid and dimethyl sulfoxide, and the concentration of terephthalic acid in the terephthalic acid mixture is 1 mM.
[0050] The W, G and numbers of the bimetallic organogel electrode materials prepared in Examples 1 to 3 are shown in Table 1.
[0051] Table 1
[0052]
[0053] Comparative Example 1
[0054] A method for preparing a metal organic gel material (number: Ni-MOG) comprises the following steps:
[0055] The transition metal nickel salt was dissolved in ethanol by ultrasound for 30 minutes to obtain a green transparent transition metal salt solution. Under a nitrogen atmosphere, a colorless transparent terephthalic acid mixture was placed in a round-bottom flask and stirred for 30 minutes under a 70°C heating jacket. During the stirring process, the transition metal salt solution was slowly added dropwise to the terephthalic acid mixture at 70°C by a hot injection method, and the solvent thermal reaction was continued at 70°C for 3 hours under stirring to obtain a uniform colloidal suspension. The suspension was centrifuged to obtain a precipitate, and the precipitate was washed 5 times each with ethanol and dimethyl sulfoxide. After washing, the material is dried in vacuum at 85°C for 20 hours to obtain a metal organic gel material, wherein, in terms of molar fractions, the ratio of nickel (Ni) in the transition metal nickel salt to terephthalic acid in the terephthalic acid mixture is 1:1, the transition metal nickel salt is nickel nitrate hexahydrate, the ratio of the molar fraction of nickel in the transition metal nickel salt to the volume fraction of ethanol is 1:20, the unit of the molar fraction is mmol, the unit of the volume fraction is mL, the terephthalic acid mixture is a mixture of terephthalic acid and dimethyl sulfoxide, and the concentration of terephthalic acid in the terephthalic acid mixture is 1 mM.
[0056] Comparative Example 2
[0057] A preparation method of a metal organic gel material (code: Co-MOG) is basically the same as that of comparative example 1, except that a transition metal salt solution is used. The preparation method of the transition metal salt solution of this comparative example is as follows: dissolving a transition metal cobalt salt (the transition metal cobalt salt is cobalt nitrate hexahydrate) in ethanol by ultrasonication for 30 minutes to obtain a pink transparent transition metal salt solution. In terms of the molar fractions, the ratio of cobalt (Co) in the transition metal cobalt salt to terephthalic acid in a terephthalic acid mixture is 1:1, the ratio of the molar fraction of cobalt in the transition metal cobalt salt to the volume fraction of ethanol is 1:20, the unit of the molar fraction is mmol, and the unit of the volume fraction is mL.
[0058] Comparative Example 3
[0059] A method for preparing a metal organic compound material (number: Ni-MOC) comprises the following steps:
[0060] The transition metal nickel salt was dissolved in ethanol by ultrasonication for 30 minutes to obtain a green transparent transition metal salt solution. The colorless transparent terephthalic acid mixture was placed in a round-bottom flask under a nitrogen atmosphere and stirred at room temperature for 30 minutes. During the stirring process, the transition metal salt solution was slowly added dropwise to the terephthalic acid mixture at 20-25°C, and the reaction was continued by stirring at room temperature for 3 hours to obtain a suspension. The suspension was centrifuged to obtain a small amount of precipitate. The precipitate was washed 5 times with ethanol and dimethyl sulfoxide respectively, and then vacuum-dried at 85°C. After drying for 20 hours, a metal organic compound material is obtained, wherein, by molar fraction, the ratio of nickel (Ni) in the transition metal nickel salt to terephthalic acid in the terephthalic acid mixture is 1:1, the transition metal nickel salt is nickel nitrate hexahydrate, the ratio of the molar fraction of nickel in the transition metal nickel salt to the volume fraction of ethanol is 1:20, the unit of the molar fraction is mmol, the unit of the volume fraction is mL, the terephthalic acid mixture is a mixture of terephthalic acid and dimethyl sulfoxide, and the concentration of terephthalic acid in the terephthalic acid mixture is 1 mM.
[0061] Comparative Example 4
[0062] A preparation method of a metal organic compound material (number: Co-MOC) is basically the same as that of comparative example 3, except that the transition metal salt solution is prepared by: dissolving a transition metal cobalt salt (the transition metal cobalt salt is cobalt nitrate hexahydrate) in ethanol by ultrasound for 30 minutes to obtain a pink transparent transition metal salt solution, wherein, by amount of substance, the ratio of cobalt (Co) in the transition metal cobalt salt to terephthalic acid in a terephthalic acid mixture is 1:1, and the ratio of the amount of cobalt in the transition metal cobalt salt to the volume of ethanol is 1:20, the unit of amount of substance is mmol, and the unit of volume is mL.
[0063] Comparative Example 5
[0064] A method for preparing a bimetallic organic compound material (number: NiCo-MOC) comprises the following steps:
[0065] A transition metal nickel salt, a transition metal cobalt salt and ethanol are mixed and ultrasonicated for 30 minutes to dissolve the transition metal nickel salt and the transition metal cobalt salt in the ethanol to obtain a brown transparent transition metal salt mixture. Under a nitrogen atmosphere, a colorless transparent terephthalic acid mixture is placed in a round-bottom flask and stirred at room temperature for 30 minutes. Under stirring, the transition metal salt mixture is slowly added dropwise to the terephthalic acid mixture, and stirring is continued at room temperature for 15 minutes. Subsequently, a solvent thermal reaction is carried out at 70° C. for 3 hours under stirring to obtain a suspension. The suspension is centrifuged to obtain a small amount of precipitate. The precipitate is washed 5 times with ethanol and dimethyl sulfoxide respectively. After washing, the precipitate is washed 5 times with ethanol and dimethyl sulfoxide respectively. The material is dried at 85° C. in vacuum for 20 h to obtain a bimetallic organic compound material, wherein, by molar fraction, the ratio of nickel (Ni) in the transition metal nickel salt, cobalt (Co) in the transition metal cobalt salt and terephthalic acid in the terephthalic acid mixture is 1:1:2, the transition metal nickel salt is nickel nitrate hexahydrate, the transition metal cobalt salt is cobalt nitrate hexahydrate, the ratio of the molar fraction of nickel in the transition metal nickel salt to the volume fraction of ethanol is 1:40, the unit of the molar fraction is mmol, the unit of the volume fraction is mL, the terephthalic acid mixture is a mixture of terephthalic acid and dimethyl sulfoxide, and the concentration of terephthalic acid in the terephthalic acid mixture is 1 mM.
[0066] Figure 1 The SEM images of the bimetallic organic gel electrode materials prepared in Examples 1 to 3 are as follows: Figure 1 (a) is Example 1, Figure 1 (b) is Example 2, Figure 1 (c) is Example 3. Figure 1 It can be seen that the bimetallic organic gel electrode materials prepared in Examples 1 to 3 are all rod-shaped with smooth surfaces and similar diameters, but the particle size of the bimetallic organic gel electrode material prepared in Example 1 is significantly larger than that of the bimetallic organic gel electrode materials prepared in Examples 2 to 3.
[0067] Figure 2 HRTEM images of the bimetallic organic gel electrode materials prepared in Examples 1 to 3, wherein: Figure 2 (a) is Example 1, Figure 2 (b) is Example 2, Figure 2 (c) is Example 3. Figure 2 It can be seen that the surfaces of the bimetallic organic gel electrode materials prepared in Examples 1 to 3 all show ribbon-like curved stripes. This is because Ni and Co form aromatic layers after coordination with the O atoms on the carboxyl groups of terephthalic acid. After coordination, slightly distorted octahedral units are formed, showing stronger electronic interactions, resulting in lattice distortion and the formation of a long-range ordered and short-range disordered structure, which will expose more active sites and increase the number of unsaturated metal sites.
[0068] Figure 3 The XRD patterns of the bimetallic organic gel electrode materials prepared in Examples 1 to 3 and the metal organic gel materials prepared in Comparative Examples 1 to 2 are shown in FIG. Figure 3 It can be seen that the bimetallic organogel electrode materials prepared in Examples 1 to 3 and the metal organogel materials prepared in Comparative Examples 1 to 2 have similar crystal structures and basically the same diffraction angles. Among them, the metal organogel materials prepared in Comparative Examples 1 to 2 are single metal coordination, and their diffraction intensity is low and their crystallinity is poor.
[0069] Figure 4 The FTIR images of the bimetallic organic gel electrode materials prepared in Examples 1 to 3 are shown in FIG. Figure 4 It can be seen that the bimetallic organic gel electrode material prepared in Example 1 has a -1 The vibration peak at 1687 cm -1 The vibration peak at 1325 cm -1 The vibration peak at 915 cm is attributed to the OH bond in the ligand and -1 The vibration peak at 456 cm is attributed to the corresponding CC bond in the ligand. -1 The corresponding absorption peaks are the bonding absorption peaks of metal (Ni and Co) and oxygen (O), which proves that the metal coordinates with the carboxylic acid site of terephthalic acid to form metal organic gel.
[0070] Figure 5 The Raman graphs of the bimetallic organometallic gel electrode materials prepared in Examples 1 to 3 are shown in FIG. Figure 5 It can be seen that at 2920cm -1 and 1047cm -1 The corresponding positions are CH bonds and aromatic rings in the ligand.
[0071] Figure 6 This is the element distribution mapping characterization diagram of the bimetallic organic gel electrode material prepared in Example 1. Figure 6 It can be seen that the Co element and the Ni element are evenly distributed on the surface of the bimetallic organic gel electrode material prepared in Example 1. Figures 1 to 6 , indicating that the bimetallic organic gel electrode material prepared in Example 1 was successfully synthesized.
[0072] Example 5
[0073] Three-electrode system: 1 mol L -1Potassium hydroxide (KOH) solution (KOH solution is a mixture of KOH and water) is used as an electrolyte, and the electrode active material is coated on the nickel foam as a working electrode (coating method: 3 mg of electrode active material, 7 mg of carbon black, 965 μL of isopropanol and 35 μL of Nafion solution (5 wt%) are mixed evenly, coated on the nickel foam, and dried to obtain a working electrode, wherein the loading amount of the electrode active material on the working electrode is 0.3 mg cm -2 ), with Hg / HgO as the reference electrode and platinum as the counter electrode, linear sweep voltammetry (LSV) was performed at 5 mV s -1 An LSV polarization curve is obtained at a scanning rate of, wherein the electrode active material is one of the bimetallic organic gel electrode materials prepared in Examples 1 to 3, the metal organic gel materials prepared in Comparative Examples 1 to 2, the metal organic compound materials prepared in Comparative Examples 3 to 4, and the bimetallic organic compound materials prepared in Comparative Example 5.
[0074] According to the literature (Stable hydrogen evolution reaction at high current densities via designing the Ni single atoms and Ru nanoparticles linked by carbonbridges, Nature Communications volume 15, Article number: 2218 (2024)), it is known that the hydrogen evolution reaction occurs in the voltage range of -0.8 to 0.0 V (versus. RHE). The hydrogen evolution reaction-polarization curves (HER-LSV) of the bimetallic organogel electrode materials prepared in Examples 1 to 3 as electrode active materials are shown in FIG. Figure 7 As shown, the metal organic gel materials prepared in Comparative Examples 1 to 2, the metal organic compound materials prepared in Comparative Examples 3 to 4, and the bimetallic organic compound materials prepared in Comparative Example 5 are respectively used as electrode active materials. The hydrogen evolution reaction-polarization curves (HER-LSV) are as follows Figure 8 As shown, when the current density reaches 10 mA cm -2 When the hydrogen evolution overpotential (corresponding to Figure 7 and Figure 8 -10mA cm on the vertical axis -2 The absolute value of the horizontal axis at the time of
[0075] Table 2
[0076] Example / Comparative Example Hydrogen evolution overpotential (unit: mV) Example 1 28mV Example 2 43mV Example 3 69mV Comparative Example 1 165mV Comparative Example 2 181mV Comparative Example 3 376mV Comparative Example 4 400mV Comparative Example 5 307mV
[0077] As shown in Table 2, the hydrogen evolution overpotentials of the bimetallic organogel electrode materials prepared in Examples 1 to 3 are all low, and the hydrogen evolution overpotential of the bimetallic organogel electrode material prepared in Example 1 is the lowest. This may be due to the difference in the atomic radius of the bimetallic atoms, which causes tensile strain in the overall structure, resulting in more defects and a larger specific surface area, thereby increasing the reaction intermediates (such as H + ions) contact with the working electrode surface and promote the electron transport process inside it, effectively increasing the HER reaction kinetics. The metal organic compound materials prepared in Comparative Examples 3 to 4 and the bimetallic organic compound materials prepared in Comparative Example 5 have extremely high hydrogen evolution overpotentials, which may be due to the poor crystallinity of the metal organic compound materials caused by the solvothermal reaction and the low temperature during the dropwise addition, and the chaotic internal structure and the gel-like appearance are not obvious, so the conductivity is low and the yield is also low.
[0078] The current obtained by the above linear sweep voltammetry (LSV) test is processed logarithmically to obtain the Tafel curve of electrocatalytic hydrogen evolution. The Tafel curve is as follows: Fig. 9 , Fig.10 and Fig.11 As shown in Table 3, the Tafel slope is shown in Table 3. It can be seen from Table 3 that the metal organic gel materials prepared in Comparative Examples 1 to 2, the metal organic compound materials prepared in Comparative Examples 3 to 4, and the bimetallic organic compound materials prepared in Comparative Example 5 have a larger Tafel slope for electrocatalytic hydrogen evolution, and the Tafel slopes of the bimetallic organic gel electrode materials prepared in Examples 1 to 3 are all relatively low. Among them, the bimetallic organic gel electrode material prepared in Example 1 has the smallest Tafel slope of 62.1 mVdec. -1 , indicating faster HER reaction kinetics.
[0079] Table 3
[0080]
[0081] The bimetallic organic gel electrode material prepared in Example 1, the metal organic gel material prepared in Comparative Examples 1-2, the metal organic compound material prepared in Comparative Examples 3-4, and the bimetallic organic compound material prepared in Comparative Example 5 were respectively used as electrode active materials to assemble into a "three-electrode system" for hydrogen evolution stability test. -2 The electrode voltage change is tested under current density to obtain the hydrogen evolution reaction voltage test diagram, such as Fig.12 , Fig.13 and Fig.14 As shown by Fig.12 It can be seen that the three-electrode system using the bimetallic organic gel electrode material prepared in Example 1 remains stable after 175 hours. Fig.13 It can be seen that after 10 hours of testing, the electrode voltage of the three-electrode system using the metal organic gel material prepared in Comparative Example 1 decreased by 50 mV, the electrode voltage of the three-electrode system using the metal organic gel material prepared in Comparative Example 2 decreased by 52 mV, and the electrode voltage of the three-electrode system using the metal organic compound material prepared in Comparative Example 3 decreased by 88 mV, so their stability was poor. The three-electrode system using the metal organic compound material prepared in Comparative Example 4 could only run for 5 hours. Fig.14 It can be seen that the three-electrode system using the bimetallic organic compound material prepared in Comparative Example 5 operated for 4 hours before the electrode voltage stabilized to 293 mV. After continuing to operate for 6 hours, the electrode voltage dropped by 73 mV, and its stability was poor.
[0082] The bimetallic organogel electrode material prepared in Example 1 was used as the electrode active material to assemble the aforementioned “three-electrode system” at 100 mA cm -2 , 200mA cm -2 , 400mA cm -2 and 200mA cm -2 The current density was cycled sequentially and periodically, and each current density was operated for 5 hours to test the electrode voltage stability at different current densities. Fig.15 As shown, Fig.15 The potential diagram of the bimetallic organic gel electrode material prepared in Example 1 at different current densities is shown in FIG. Fig.15 It can be seen that the three-electrode system using the bimetallic organic gel electrode material prepared in Example 1 still maintains stability at the 65th hour of the cycle under the conditions of switching different current densities, proving that the bimetallic organic gel electrode material prepared in Example 1 has excellent durability and excellent rate performance in HER.
[0083] According to the literature (Exceptional catalytic activity of oxygen evolution reaction via two-dimensional graphene multilayer confined metal-organic frameworks, Nature Communications, 13, Article number: 6171 (2022)), it is known that oxygen evolution reaction occurs in the voltage range of 1.2 to 2.0 V (versus. RHE). Fig.16 The oxygen evolution reaction-polarization curve (OER-LSV) of the bimetallic organic gel electrode material prepared in Examples 1 to 3. Fig.16 It can be seen that at a current density of 10 mA cm -2The oxygen evolution overpotential of the bimetallic organic gel electrode material prepared in Example 1 (oxygen evolution overpotential = abscissa value - 1.23) is 306 mV, the oxygen evolution overpotential of the bimetallic organic gel electrode material prepared in Example 2 is 345 mV, and the oxygen evolution overpotential of the bimetallic organic gel electrode material prepared in Example 3 is 360 mV.
[0084] Fig.17 The EIS impedance test graphs of the bimetallic organic gel electrode materials prepared in Examples 1 to 3 and the metal organic gel materials prepared in Comparative Examples 1 to 2 are shown in Figure 1. Fig.17 The impedance fitting analysis shows that the charge transfer resistance (R ct ) is 12.0Ω, and the charge transfer resistance (R ct ) is 14.4Ω, and the charge transfer resistance (R ct ) is 17.5Ω, and the charge transfer resistance (R ct ) is 26.1Ω, and the charge transfer resistance (R ct ) is 32.6Ω, wherein the charge transfer resistance of the bimetallic organic gel electrode material prepared in Example 1 is the smallest, and therefore the conductivity of the bimetallic organic gel electrode material prepared in Example 1 is the highest, which may be due to the introduction of holes by the metal-induced coordination environment, which can effectively adjust the conductivity of the bimetallic organic gel electrode material. Therefore, the bimetallic organic gel electrode material prepared in Example 1 can further adjust its electronic structure and electron cloud distribution through the interaction between the bimetallic atoms, thereby improving the conductivity, reducing the adsorption energy of the reaction intermediates, and thus improving its catalytic activity.
[0085] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A method for preparing a bimetallic organic gel electrode material, characterized in that: The following steps are involved: A transition metal nickel salt and a transition metal cobalt salt are dissolved in ethanol to obtain a transition metal salt mixed solution. The transition metal salt mixed solution is added dropwise to a terephthalic acid mixed solution at 70 to 90° C. under a nitrogen or inert gas atmosphere, and the solvent thermal reaction is continued at 70 to 90° C. for 3 to 5 hours to obtain a colloidal suspension. The suspension is centrifuged to obtain a precipitate, which is washed and vacuum dried to obtain a bimetallic organic gel electrode material, wherein the ratio of nickel in the transition metal nickel salt, cobalt in the transition metal cobalt salt and terephthalic acid in the terephthalic acid mixed solution is x:y:(x+y), x=1 to 2, y=1 to 2.
2. The preparation method according to claim 1, characterized in that: The transition metal cobalt salt is cobalt nitrate hexahydrate or cobalt chloride, and the transition metal nickel salt is nickel nitrate hexahydrate or nickel chloride.
3. The preparation method according to claim 1, characterized in that: The ratio of the molar fraction of nickel in the transition metal nickel salt to the volume fraction of ethanol is (1-2):(20-60), the unit of the molar fraction is mmol, and the unit of the volume fraction is mL.
4. The preparation method according to claim 1, characterized in that: The terephthalic acid mixed liquid is a mixture of terephthalic acid and dimethyl sulfoxide, and the concentration of terephthalic acid in the terephthalic acid mixed liquid is 0.5-1 mM.
5. The preparation method according to claim 1, characterized in that: The transition metal nickel salt and the transition metal cobalt salt are dissolved in ethanol by ultrasonication for 30 to 60 minutes.
6. The preparation method according to claim 1, characterized in that: The terephthalic acid mixture is first stirred at 70-90° C. for at least 30 minutes, and then the transition metal salt mixture is added dropwise to the terephthalic acid mixture at 70-90° C. by hot injection. The terephthalic acid mixture is kept stirred when the transition metal salt mixture is added dropwise to the terephthalic acid mixture.
7. The preparation method according to claim 1, characterized in that: The nitrogen or inert gas atmosphere is achieved by replacing the nitrogen or inert gas at least three times, wherein the operation of replacing the nitrogen or inert gas includes: evacuating to -0.1 to -0.01 MPa, and introducing nitrogen or inert gas.
8. The preparation method according to claim 1, characterized in that: The washing operation comprises: centrifuging the precipitate 3 to 5 times with ethanol and dimethyl sulfoxide in sequence; The vacuum drying temperature is 60-90° C., and the vacuum drying time is 12-24 hours.
9. The bimetallic organic gel electrode material obtained according to the preparation method according to any one of claims 1 to 8.
10. Use of the bimetallic organic gel electrode material according to claim 9 in hydrogen evolution or oxygen evolution.
Citation Information
Patent Citations
Carbon based bimetallic composite material, preparation and application thereof
CN107803207A
Preparation and application of MOF-guided nickel-cobalt bimetallic phosphide
CN111111716A
Metal organogel catalyst synthesized by using double ligand regulation and control as well as preparation and application of metal organogel catalyst
CN117254045A
Preparation method for modified cathode of MEC-AD system and application of system with high efficiency and low energy consumption
US12145873B1
Metal organic framework materials and application thereof in electrocatalysis
WO2024009289A2